Splenic B1 B Cells Acquire a Proliferative and Anti-Inflamatory Profile During Pregnancy in Mice - Valeff, Natalin J.; Ventimiglia, María S.; Dibo, Marcos; Markert, Udo R.; Jensen, Federico (Frontiers in Immunology, 2022)
B cells are a heterogeneous cell population with differential ontogeny, anatomical location, and functions. B1 B cells are a distinct subpopulation characterized by their unique capacity of self-renewal, the production of large quantities of IL-10, and the ability to secrete protective, anti-inflammatory natural antibodies (NAbs), presumably upon down-regulation of CD1d expression. Although natural antibodies are thought to be protective, due to their polyreactivity, their participation in certain autoimmune diseases has been suggested. In the context of pregnancy, the role of B1 B cells has been discussed controversially. While in human pregnancies B1 B cells and natural/polyreactive antibodies they produce are involved in the development of preeclampsia, in mice they promote healthy gestation and fetal protection. In this work, we aimed to functionally characterize the splenic B1 B cell population during pregnancy in mice. Functional enrichment analysis using only up-regulated transcripts from a transcriptomic profile performed on total splenic B cells from pregnant compared to non-pregnant mice showed augmented cell cycle and DNA replication pathways. Proliferation studies by flow cytometry showed augmented Ki-67 proliferation marker expression and percentages of B1 B cells. Furthermore, B1 B cells produced higher levels of IL-10 and lower levels of TNF- leading to an increased IL-10/ TNF- ratio and showing an immunoregulatory phenotype. Finally, we observed lower expression of CD1d on B1 B cells, suggesting a higher capacity to produce NAbs in the context of pregnancy. In summary, our results showed not only an expanded and proliferative splenic B1 B cell population during pregnancy but also the acquisition of immunomodulatory capacities suggesting its critical role in the intricate process of pregnancy tolerance.